Nguyễn Châm Anh
3 tháng 8 2017 lúc 20:19

=\(\frac{1-\sqrt{2}}{\left(1+\sqrt{2}\right)\left(1-\sqrt{2}\right)}\)+\(\frac{\sqrt{2}-\sqrt{3}}{\left(\sqrt{2}+\sqrt{3}\right)\sqrt{2}-\sqrt{3}}\)+.....+\(\frac{\sqrt{99}-\sqrt{100}}{\left(\sqrt{99}+\sqrt{100}\right).\left(\sqrt{99}-\sqrt{100}\right)}\)

=\(\frac{1-\sqrt{2}}{1-2}+\frac{\sqrt{2}-\sqrt{3}}{2-3}+...+\frac{\sqrt{99}-\sqrt{100}}{99-100}\)

=\(\sqrt{2}-1+\sqrt{3}-\sqrt{2}+....+\sqrt{100}-\sqrt{99}\)

=\(-1+\sqrt{100}\)

=9

Bình luận (0)

học tốt nhé

Bình luận (0)

hello

cần j ko?

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN